POOR PROGNOSTIC FACTORS IN PATIENTS WITH BIRDSHOT RETINOCHOROIDOPATHY. Issue 11 (November 2016) - Silpa-archa, Sukhum; Lee, Joan J.; Boonsopon, Sutasinee; Lizárraga, Marisol T.; Preble, Janine M.; Sujirarat, Dusit; Patel, Pranav; Foster, C. Stephen
Abstract : Purpose: To identify prognostic factors for poor visual outcome in patients with birdshot retinochoroidopathy. Methods: A case–control study of 98 patients with birdshot retinochoroidopathy (196 eyes) was evaluated with a follow-up period of at least 12 months. After exclusion of glaucoma, optic atrophy, and macular scar, the remaining eligible patients were categorized into two groups: poor visual outcomes and good visual outcomes. Poor visual outcome was defined as less than −6 mean deviation score on Swedish interactive threshold algorithm (SITA) short-wavelength automated perimetry (SWAP) test and abnormality (amplitude or implicit time) of 30 Hz flicker electroretinogram at 4-year follow-up and at the most recent visit for separate analysis. Potential factors between both groups were statistically analyzed by Chi-square test and logistic regression model. Results: After the aforementioned exclusion, the remaining 77 patients with an average follow-up period of 52 ± 29 months (335 person-years, 36% with follow-up of more than 5 years) were divided into two groups. Sixteen patients were categorized as having poor visual outcome. Univariate analysis identified significant association of abnormal 30 Hz flicker electroretinogram amplitude ( P = 0.004), implicit time ( P = 0.002), and SITA SWAP mean deviation at the initial visit ( P < 0.001) in the poor visual outcome group. Multivariate logistic regression analysis identified only SITA SWAP mean deviation to be associated with poor visual outcome (adjusted odds ratio, 32.50; 95% confidence interval [3.84–275.32]; P = 0.001) at the initial visit. To verify the model validity, an analysis of 42 patients at 4-year follow-up was performed and the outcome was confirmed (adjusted odds ratio, 8.80; 95% confidence interval [1.58–49.16]; P = 0.013). Conclusion: Worse SITA SWAP mean deviation at the initial visit is a predictor of poor visual outcome in patients with birdshot retinochoroidopathy, and may serve as a proxy marker for delayed effective steroid sparing therapy in patients with birdshot retinochoroidopathy. Abstract : The only predictive factor of poor visual outcome in patients with birdshot retinochoroidopathy was SITA SWAP mean deviation at the initial visit.